Nursing Assistance For Traumatic Brain Injury Patients With Intracranial Adaptive Capacity Decrease Using 30o Head Up Position Intervention At Jendral Ahmad Yani Hospital Metro City - Tasmadi; Wardoyo, Eko; Sugiarto, Sugiarto (INDOGENIUS, 2025)
Background & Objective: A head injury is a traumatic disruption of brain function with or without interstitial hemorrhage in the brain substance without a break in brain continuity. The purpose of this study was to determine Nursing Care for Traumatic Brain Injury Patients with Decreased Intracranial Adaptive Capacity Using the 30⁰ Head Up Position Intervention. Method: The method in this scientific work with a descriptive approach to nursing care involving 2 head injury patients, the instrument used is an assessment sheet, the application of the 30⁰ Head Up position is carried out for 4 days in patients 1 and 2, with the intensity of giving the 30⁰ Head Up position 3 times a day for 30 minutes. Result: The results of this study found that the main problem that arose in both patients was a decrease in intracranial adaptive capacity, the intervention that was arranged was intracranial management combined with giving the Head Up 30⁰ position, implementation was carried out for 4 days, nursing evaluation of intracranial decline improved to 2 in the first patient and day 3 in the second patient. Conclusion: The recommendation that the author can give is that the application of the Head Up 30⁰ position can restore intracranial decline quickly.